THE INFLUENCE OF SUPERPLASTICISERS ON THE FRESH AND MECHANICAL BEHAVIOUR OF FOAM CONCRETE UTILIZING POFA AS SAND REPLACEMENT (Jurnal Teknologi (Sciences & Engineering), 2020)
Since the foam concrete is delicate, it is important to carefully choose the additives, such as superplasticiser (SP), to be used in this type of concrete. The effect of using different types and percentages of SP on the performance of foam concrete with target density of 1500±50 kg/m3 has been investigated in this study. A sustainable material, Palm Oil fuel ash (POFA), used as a sand replacement at a level of 20% by weight. Five types of SP have been used in this study, including Sulphonated polymer-based, selected synthetic and organic polymers-based and three Polycarboxylate ether-based (PCE). Different SP contents (0.0%, 1.0% and 2.0%) have been used as a ratio of cement weight. Workability, consistency, foam stability and mechanical properties were investigated. The results showed that types and quantity of SP have a significant effect on the different properties of the foam concrete. Workability, compression strength and tension strength improved remarkably for most specimens. The use of 2% SP4, a PCE SP, showed superior workability, compression strength and tensile strength with acceptable stability.